Determinants of hypertensive crisis among hypertensive patients at adult emergency departments of public hospitals in Addis Ababa, Ethiopia, 2021: a case–control study - Hailemariam Gezie; Aklilu Azazh; Birhanu Melaku; Habtam Gelaye (International Journal of Emergency Medicine, 2023)
Abstract Background Hypertension (HTN) is a major global health problem that affects approximately 1.13 billion people worldwide, and 1–2% of this population has hypertensive crisis. Hypertensive crisis is becoming a major health issue in low-income countries. However, few studies have been conducted in developing countries such as Ethiopia. This study aimed to assess the determinants of hypertensive crisis among patients visiting adult emergency departments of public hospitals in Addis Ababa. Method A hospital-based unmatched case–control study was conducted among 85 cases with a hypertensive crisis and 170 controls with hypertension without a hypertensive crisis in the adult emergency departments of public hospitals in Addis Ababa from March 15 to May 15, 2021. Data were collected using a structured questionnaire and analyzed using SPSS version 26. Binary logistic regression and multivariable logistic regression were performed. Finally, a statistically significant level was declared at a p value of less than 0.05. The result was summarized and presented in text, tables, and graph. Result The odds of having hypertensive crisis were 3.6 times (AOR = 3.621) higher among participants with a history of hypertension compared to those without a history of hypertension. There was also 4 times increased risk of hypertensive crisis among participants who presented with diabetes mellitus than participants who presented without it (AOR = 4.179). Similarly, participants who presented with stroke had 7 times higher odds of having hypertensive crisis (AOR = 7.174) than participants without stroke. Conclusion This study demonstrated a statistically significant association between unemployment, diabetes mellitus, stroke, heart failure, history of hypertension, family history of hypertension, and regular follow-up with a hypertensive crisis. The Ethiopian Ministry of Health, Ababa City Administration Health Bureau, and hospitals shall give due attention to the HTN crisis. Health care workers, hospital managers, and other stakeholders shall work towards the early detection and management of HTN-crisis to prevent related morbidity, disability, and mortality.